‘Poems look like a mathematical equation’: Assessment in poetry education - Xerri, Daniel (International Journal of English Studies, 2016)
This article considers the influence that assessment exerts on poetry education. By means of research conducted in a post-16 educational context in Malta, it shows that teachers’ and students’ practices in the poetry lesson are determined by the kind of examinations that candidates sit for. When the mode of assessment is constituted solely by the traditional essay test that excludes students’ personal response, their engagement with poetry might be impaired and teachers’ role becomes highly pronounced. The article demonstrates how assessment plays a key role in governing teachers’ and students’ practices in the classroom. However, it is also argued that other factors are equally responsible for their approach to poetry.